Indocyanine green fluorescence-navigated laparoscopic metastasectomy for peritoneal metastasis of hepatocellular carcinoma: a case report - Yoshihiro Miyazaki; Masanao Kurata; Yukio Oshiro; Osamu Shimomura; Kazuhiro Takahashi; Tatsuya Oda; Nobuhiro Ohkohchi (Surgical Case Reports, 2018)
Abstract Background Indocyanine green (ICG) can selectively accumulate in primary hepatocellular carcinoma (HCC) and its extrahepatic metastases. ICG fluorescence imaging is an extremely sensitive intraoperative tool for detecting HCC foci and can be used to detect impalpable tumors in laparoscopic surgery. Here, we report a case of a 75-year-old man who underwent peritoneal metastasis resection of HCC using a laparoscopic near-infrared imaging system and ICG fluorescence-navigated surgery. Case presentation A 75-year-old man was referred to our department for peritoneal metastasis resection of HCC. Two years before admission, he had undergone transarterial embolization and segmentectomy of segment 6 with open surgery for ruptured HCC. Computed tomography revealed a 12-mm peritoneal metastatic lesion on the abdominal wall near the cut surface of the liver. No other metastases were observed; resection of the solitary metastasis was scheduled. ICG (0.5 mg/kg body weight) was intravenously injected, 72 h preoperatively. An endoscopic, ICG near-infrared fluorescence imaging system revealed clear green fluorescence, indicating peritoneal metastasis of HCC on the abdominal wall. The tumor was resected with adequate surgical margin by partially resecting the liver and diaphragm, followed by histological confirmation as peritoneal metastasis of HCC. No recurrence was observed after 12 months of follow-up. Conclusions ICG fluorescence can be useful in laparoscopic surgery for identifying peritoneal metastasis.